Chiral Emission from Optical Metasurfaces and Metacavities - Jungho Han; Heejoo Jang; Yeonsoo Lim; Seongheon Kim; Jeheon Lee; Young Chul Jun (Advanced Photonics Research)
Chiral emission exhibiting a large degree of circular polarization (DCP) is important in diverse applications ranging from displays and optical storage to optical communication, bioimaging, and medical diagnostics. Although chiral luminescent materials can generate chiral emissions directly, they frequently suffer from either low DCP or low quantum efficiencies. Achieving high DCP and quantum efficiencies simultaneously remains extremely challenging. This review introduces an alternative approach to chiral emission. Chiral emission with large DCP can be readily achieved by combining conventional achiral emitters with chiral metasurfaces. Particularly, this article focuses on recent experimental and theoretical studies on perovskite metasurfaces and metacavities that employ achiral perovskite materials. First, chiral photoluminescence from extrinsic and intrinsic perovskite metasurfaces is explained together with theoretical discussions on metasurface design based on reciprocity and critical coupling. Chiral photoluminescence from other achiral materials is also explained. Subsequently, chiral electroluminescence from perovskite metacavities and other achiral materials is discussed. Finally, it is concluded with future perspectives. This review provides physical insights into how ideal chiral emission can be realized by optimizing the design of metasurfaces and metacavities. Compact chiral light sources with both near‐unity DCP and strong emission intensities can have far‐reaching consequences in a wide range of future applications.